The Influence of the Example Non Example Model on Student Learning Participation in Social Studies - Khadafi, Muhammad; Aramuddin, Aramuddin; Hamdani, M. Fikri; Risnawati, Risnawati (Journal of Islamic Education Students (JIES), 2024)
This research examines the influence of the Example Non Example learning model on student participation in social studies, driven by the low levels of engagement observed among students. This study aims to assess the effectiveness of the Example Non Example model in enhancing student participation in social studies classes. A quasi-experimental method was employed, involving two groups: an experimental group taught using the Example Non Example model and a control group receiving conventional instruction. The model incorporates visual media, with only the experimental group exposed to image-based learning materials. A total of 30 students were included in the sample, selected through total sampling. Data were collected using an observation sheet for student participation. The findings indicate a significant effect of the Example Non Example model on student participation at SDN 06 Tanjung Baru Tanah Datar. Statistical analysis, including the t-test and determination test, showed a t-test value of 0.401, which is below the threshold of 0.05, suggesting a meaningful impact. The determination test further revealed that this model accounts for 14% of the variance in student participation.